Analisis Efisiensi Penggunaan Faktor Produksi Usaha Tani Ubi Kayu Di Desa Kotabumi Udik Kabupaten Lampung Utara - Rani Lestari, Astria; Fitriani, Fitriani; Humaidi, Edy; Noer, Irmayani (Politeknik Negeri Lampung, 2024)
Cassava (Manihot esculenta Crantz) is a source of carbohydrates that has a strategic position as a raw material for food, animal feed, and various food and non-food industries. Land area, production and productivity of cassava in Lampung Province has decreased year by year. North Lampung is the largest cassava producing district in Lampung by producing cassava of 959,279 tons with an average cassava productivity yield of more than 25 tons per hectare every year. So this research was conducted to analyze the effect of using cassava production factors simultaneously and partially and analyze the allocation efficiency level of the use of cassava production factors in Kotabumi Udik Village, North Lampung Regency. The analysis technique used in this research was Coub-Douglass to determine the dominant and efficient factors of production. The results showed that the factors of production of cassava farming, comprising land area, seeds, fertilizers, pesticides, and labor, simultaneously had a significant effect on cassava production. The use of production factors for cassava farming in Kotabumi Udik Village, Kotabumi District, North Lampung Regency was not yet efficient.